Industrial training report: NCC Automobile Sdn Bhd / Mohamad Na'im Bahari @ Tak - Bahari @ Tak, Mohamad Na'im (Universiti Teknologi MARA, Perlis, 2023)
This industrial training report is written based on my internship journey as Sales Administration at NCC Automobile Sdn Bhd (Perodua 4s Kampar) Perak. I started my journey at the company from 29 August 2022 until 10 February 2023. Before this, I did not have any experience working in administration field and my internship position in this company is Sales Administration, then it was different from my courses which is Human Resource Management but I can use all the knowledge that I got from my studies and practice while working as Sales Administration. NCC Automobile Sdn. Bhd. has four department which are services, insurance, body and paint and sales administration. Due to my scope of duties and responsibilities dissimilar from my courses, so I was too excited to learn and gain new knowledge at there. As you know this company was non-government sectors, I will do all the tasks likes other permanent workers and it was a good opportunities for me to acquire new things at there. Sometimes, I got a task from insurances and services department